1992
DOI: 10.1161/01.cir.85.4.1286
|View full text |Cite
|
Sign up to set email alerts
|

Relation of plasma lipid and apoprotein levels to progressive intimal hyperplasia after arterial endarterectomy.

Abstract: Elevated lipid levels usually associated with an increased risk of atherosclerosis may predispose patients to an increased incidence of intimal hyperplasia after endarterectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0
2

Year Published

1992
1992
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 24 publications
1
8
0
2
Order By: Relevance
“…[25][26][27][28][29][30] An inverse relationship between restenosis after percutaneous coronary transluminal angioplasty and restenosis after carotid endarterectomy has also been demonstrated in some, but not all, studies. [31][32][33][34] There are, however, several exceptions to this general rule that should be mentioned. For example, some genetically determined low HDL states due to mutations in apolipoprotein A-I are not associated with an increased risk of atherosclerosis.…”
Section: Relationship Of Hdl/apolipoprotein A-i To Atherosclerosis Anmentioning
confidence: 99%
“…[25][26][27][28][29][30] An inverse relationship between restenosis after percutaneous coronary transluminal angioplasty and restenosis after carotid endarterectomy has also been demonstrated in some, but not all, studies. [31][32][33][34] There are, however, several exceptions to this general rule that should be mentioned. For example, some genetically determined low HDL states due to mutations in apolipoprotein A-I are not associated with an increased risk of atherosclerosis.…”
Section: Relationship Of Hdl/apolipoprotein A-i To Atherosclerosis Anmentioning
confidence: 99%
“…The genetic polymorphism of ApoE results from the existence of three alleles (ε2, ε3 and ε4) encoding three proteins (E2, E3 and E4) and combining in six different genotypes (ε2/ε2, ε2/ε3, ε2/ε4, ε3/ε3, ε3/ε4, ε4/ε4) [1]. Studies have suggested that ApoE-ε4 genotype predisposes to the early development of atherosclerosis [2,3,4,5,6] and coronary artery disease [7,8,9]. Associations between ApoE-ε4 and Alzheimer’s disease [10, 11], cerebral hemorrhage [12, 13] and poststroke dementia have also been reported [14].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, nearly half of all patients with coronary artery disease have low HDL-C (2, 3). Low HDL-C appears to be associated with, among other factors, an enhanced risk of angioplasty restenosis (4) and with a number of clinical syndromes such as the "metabolic syndrome", which combines low HDL with hypertriglyceridemia and abdominal obesity (5). Raising HDL-C concentrations may have therapeutic value in reducing risk of reinfarction and stroke in coronary patients (6,7).…”
mentioning
confidence: 99%